Single-Center Retrospective Analysis of Acute Type A Aortic Dissection Outcome and Reoperation Focusing on Extended Versus Limited Initial Repair - Elbayomi, Mohamed; Weyand, Michael; Pathare, Presheet; Nooh, Ehab; Harig, Frank (Heart Surgery Forum, 2023)
Background: The optimal management strategy for acute aortic type A dissection remains controversial. Whether a limited primary (index) repair would increase the need for late aortic reintervention is still an open debate.Methods: A total of 393 consecutive adult patients with acute type A aortic dissection who underwent cardiac surgery were analyzed. Our research hypothesis was whether limited aortic index repair (i.e., isolated aorta ascending replace-ment without an open distal anastomosis with and without a concomitant aortic valve replacement, including hemiarch replacement procedure) is associated with a higher incidence of late aortic reoperation compared with extended repair (i.e., any other surgical procedure that goes beyond that limited approach).Results: Type of the initial repair had no statically sig-nificant relationship with in-hospital mortality with a P-value of 0.12, however in multivariable analysis, cross-clamp time had a statistically significant relation with mortality (P = 0.4). From the patients who survived until discharge (N = 311), 40 patients needed a reoperation on the aorta; the mean interval until reoperation was 4.5 years. The relationship between the type of the initial repair and the need for reoperation didn't reach a statically significant value (P = 0.9). In-hospitable mortality after the second operation was 10% (N = 4).Conclusion: We reached two conclusions. 1) An extended prophylactic repair in the initial operation of an acute type A aortic dissection might not lead to a lower incidence of reoperations on the aorta and could increase in-hospital mor-tality by increasing cross-clamp time, and 2) Reoperation on the aorta could be done safely with acceptable mortality outcomes.
CRIS-Team WoS Importer:2023-03-31